ANALISIS KEBIJAKAN PENANGGULANGAN KEMISKINAN DI BANTARAN REL KERETA API SENEN JAKARTA - Nouke A Komansilan (Master of Public Administration, Universitas Slamet Riyadi, 2014)
Poverty is a social phenomenon that is found in many societies withincountries. It is considered influenced by many factors. The aim of this study isto know the impact of poverty reduction policies undertaken by thegovernment toward the declining poverty rates and changes in the quality oflife of poor people. Research was conducted in the dwelling area at the bankof the railway at Pasar Senen, Jakarta. Result of the analysis reveals andconclude that: 1) Based on educational level of the people being studied, thepoor living along the railway mostly have low educational level and low skillthat make them only be able to engage in the informal sector works. 2) Thepoor in this region are not to live in healthy housing condition since betweenthe dwelling house and the railway is not saperated by permanent wall. 3)Based on the analysis of the policy addressing poverty reduction and theresult of identifying the suitability of the poverty reduction policy, researchresult shows that some formulated policies are not able to be implemented.This due to the some of formulated policy are not fit to the characteristics ofthe poor. 4) In implementing the program there is communication problembetween government officials with the public beneficiaries.Key words: poverty, poverty reduction policies, declining poverty rates.